Acceptability and feasibility of leveraging community‐based HIV counselling and testing platforms for same‐day oral PrEP initiation among adolescent girls and young women in Eastern Cape, South Africa. Issue 7 (24th July 2022) - Medina‐Marino, Andrew; Bezuidenhout, Dana; Ngwepe, Phuti; Bezuidenhout, Charl; Facente, Shelley N.; Mabandla, Selly; Hosek, Sybil; Little, Francesca; Celum, Connie L.; Bekker, Linda‐Gail
Abstract: Introduction: Community‐based delivery of HIV pre‐exposure prophylaxis (PrEP) to South African adolescent girls and young women's (AGYW) could increase access but needs evaluation. We integrated PrEP services via home‐based services and pop‐up tents into existing community‐based HIV testing services (CB‐HTS) in Eastern Cape Province, South Africa. Methods: After accessing CB‐HTS via a "pop‐up" tent or home‐based services, HIV‐negative AGYW aged 16–25 years were invited to complete a baseline questionnaire and referred for PrEP services at a community‐based PrEP site co‐located with pop‐up HTS tents. A 30‐day supply of PrEP was dispensed. PrEP uptake, time‐to‐initiation, cohort characteristics and first medication refill within 90 days were measured using descriptive statistics. Results: Of the 1164 AGYW who tested for HIV, 825 (74.3%) completed a questionnaire and 806 (97.7%) were referred for community‐based PrEP. Of those, 624 (77.4%) presented for PrEP (482/483 [99.8%] from pop‐up HTS and 142/323 [44.0%] from home‐based HTS), of which 603 (96.6%) initiated PrEP. Of those initiating PrEP following home‐based HTS, 59.1% initiated within 0–3 days, 25.6% within 4–14 days and 15.3% took ≥15 days to initiate; 100% of AGYW who used pop‐up HTS initiated PrEP the same day. Among AGWY initiating PrEP, 37.5% had a detectable sexually transmitted infection (STI). Although AGYW reported a low self‐perception of HIV risk, post‐hoc application of HIV risk assessment measures to available data classified most study participants as high risk for HIV acquisition. Cumulatively, 329 (54.6%) AGYW presented for a first medication refill within 90 days of accepting their first bottle of PrEP. Conclusions: Leveraging CB‐HTS platforms to provide same‐day PrEP initiation and refill services was acceptable to AGYW. A higher proportion of AGYW initiated PrEP when co‐located with CB‐HTS sites compared to those referred following home‐based HTS, suggesting that proximity of CB‐HTS and PrEP services facilitates PrEP uptake among AGYW. The high prevalence of STIs among those initiating PrEP necessitates the integration of STI and HIV prevention programs for AGYW. Eligibility for PrEP initiation should not be required among AHYW in high HIV burden communities. Community‐based service delivery will be crucial to maintaining access to PrEP services during the COVID‐19 pandemic and future health and humanitarian emergencies.